If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12x+14=26
We simplify the equation to the form, which is simple to understand
-12x+14=26
We move all terms containing x to the left and all other terms to the right.
-12x=+26-14
We simplify left and right side of the equation.
-12x=+12
We divide both sides of the equation by -12 to get x.
x=-1
| 0=-16T^2+116t+10 | | 12+2x=-36 | | -11+100=-2n-n-6n-10 | | -71=x/64 | | 4u-14=2(u-1) | | 9x^3+24x^2=0 | | 4(x+4)=2x+12 | | 0=-16T^2+116T+101 | | 3(5x+1)=108 | | 0=-16t^2+116+101 | | m+3p+4p+7m+m= | | 3y+10y-y=-13+11+2 | | -5x+26=-8(x-4) | | 0=-16t^2+101t+116 | | -2y+6=4y+12 | | 9=-5v+7(v+3) | | 130=3x+5+2x | | -3=-6y+3(y-2) | | -16t^2+116t+101= | | 30=2(u+5)-6u | | 4x+5(x-4)=34 | | x^3-15x^2=0 | | 4x+5*x-4=34 | | 2y-2.2=4.2 | | 6=-2(m+3)+m | | 6=-(m+3)+m | | 4x+6=46 | | -3w+38.7=1.2 | | y-3=x^2+4x | | y-3=x^2 | | 9(2+5)= | | y=98x^2+0.79 |